Association of peripheral nerve conduction in diabetic neuropathy with subclinical left ventricular systolic dysfunction - Mochizuki, Yasuhide; Tanaka, Hidekazu; Matsumoto, Kensuke; Sano, Hiroyuki; Toki, Hiromi; Shimoura, Hiroyuki; Ooka, Junichi; Sawa, Takuma; Motoji, Yoshiki; Ryo, Keiko; Hirota, Yushi; Ogawa, Wataru; et al. (Cardiovascular diabetology, 2015)
Background Subclinical left ventricular (LV) longitudinal myocardial systolic dysfunction occurs in patients with diabetes mellitus (DM) and preserved LV ejection fraction (LVEF), and is closely related to DM-related complications. However, the association of diabetic neuropathy (DN) with subclinical LV systolic longitudinal dysfunction in such patients has not been fully clarified. Methods The subjects of this study were 112 consecutive DM patients with preserved LVEF (all ≥50%) without coronary artery disease and overt heart failure (aged 59 ± 14 years; 60 women, 52 men). Global longitudinal strain (GLS) was determined as the average peak strain of 18 segments from the three standard apical views, and was expressed as an absolute value. DN was diagnosed by experienced diabetologists. Median, ulnar, and sural nerves were subjected to motor and sensory nerve conduction studies. F-wave latency was defined as the minimum F-wave latency after a total of 16 stimulations of the tibial nerve. Results Forty-one (37%) patients were clinically diagnosed with DN. LV functions of DM patients with and without DN were similar except for GLS being significantly smaller in patients with than in patients without DN (18 ± 2% vs. 20 ± 2%, p < 0.001). It was noteworthy that, of the parameters for the nerve conduction study, only F-wave latency correlated with GLS (r = −0.34, p < 0.001), and also was identified as an independent determinative value of GLS in a multivariate linear regression model (β = −0.25, p = 0.001) even after adjustment for other closely related GLS factors. Conclusions Monitoring of F-wave latency may aid early detection of not only DN but also subclinical LV dysfunction. Joint planning of assessment by diabetologists and cardiologists is therefore advisable for better management of DM patients.